Ingmar Persson, The Retreat of Reason: A Dilemma in the Philosophy of Life - Oscar Horta (Crítica)
Ingmar Persson, The Retreat of Reason: A Dilemma in the Philosophy of Life, Oxford University Press, Oxford, 2005, 494 pp.